Pengaruh Kajian Kitab Safinatun Najah terhadap Peningkatan Ibadah Shalat Peserta Didik: Studi di Kelas Ibtida’ Pondok Pesantren Assalafiah Al-Karimah - Zainal Abidin; Alek Maulana Pikri Padillah (Khidmatussifa: Journal of Islamic Studies, 2022)
The background of the problem from this research is the study of the Safinatun Najah book which can affect the improvement of students' prayers. The problem in this study is formulated as follows: how is the influence of the study of the book of Safinatun Najah on increasing students' prayer services. The purpose of this study was to determine the effect of the study of the book of Safinatun Najah on the improvement of students' prayers. The method used in this research is descriptive quantitative method, while the data collection techniques used are library research and field research in the form of observations, interviews, and questionnaires. The population in this study were 27 students of Ibtida 'Ponpes Assalafiah Al-Karimah. The sample used in this study is a saturated sampling technique, which is a sampling technique when all members of the population are used as samples. And the data analysis technique of this study is quantitative analysis, namely the analysis carried out by statistical analysis, namely descriptive statistics, and looking for percentages with the formula P = F/N X 100%. From the results of the research conducted, there is a positive correlation between the study of the book of Safinatun Najah towards the increase in students' prayer worship in the Ibtida' class of Ponpes Assalafiah Al-Karimah. This is indicated by the rxy value is 0.537, where the correlation index is included in the category quite strong and significant at a significant level of 5%, namely 0.396 and 1% 0.505, thus the proposed hypothesis is accepted, namely there is a positive correlation between the X variable and the Y variable. Keywords: Study of the Safinatun Najah Book and Improvement of Prayers